THE INFLUENCE OF COMMUNICATION AND WORK LIFE BALANCE ON EMPLOYEE TURNOVER INTENTION PT POLARIS ALKES STARINDO WITHWORK MOTIVATION AS VARIABLE INTERVENTION - Wanda Ramadhana; Yanita; Nurfaliza; Faisal Matriadi; Yulius Dharma (RADJA PUBLIKA, 2024)
This research aims to determine the effect of communication and work-life balance on turnover intention of PT Polaris Alkes Starindo employees, with work motivation as an intervening variable. Data was obtained from questionnaires distributed to 175 employees, and analyzed using quantitative methods with the Structural Equation Modeling (SEM) model. The research results show that communication and work-life balance have a significant effect on work motivation, as well as employee turnover intention. Apart from that, work motivation also mediates the influence of communication and work-life balance on employee turnover intention at PT Polaris Alkes Starindo.